Calibrating complexity: How complex is a gender system?. (March 2017) - Audring, Jenny
Abstract: Grammatical gender is a many-sided phenomenon, involving complex relations between semantics, morphology, phonology, and syntax. Yet, not all gender systems across the world are equally complex. This paper presents a way to assess the complexity of gender systems in natural languages, building on the typological data collected in Corbett (1991, 2013) and applying the insights from Canonical Typology (chiefly Corbett, 2006, 2012; Corbett and Fedden, 2015). The result is a typologically responsible evaluation of the ways in which grammatical gender can be more or less complex. The analysis provides a descriptive basis for the assessment of difficulty in acquisition and processing, avoiding the a priori assumption that "complex" should always equal "difficult". Moreover, the article is intended as a methodological contribution by demonstrating the set-up and use of a calibration tool for the complexity of a grammatical subsystem. Highlights: The descriptive complexity of grammatical gender systems is explored. The dimensions of cross-linguistic variation of gender systems are identified. The principles of complexity are Economy, Transparency and Independence. A tailored calibration shows that German gender is less complex than often thought.